2018
DOI: 10.1080/10962247.2018.1498410
|View full text |Cite
|
Sign up to set email alerts
|

Updating the SAPRC Maximum Incremental Reactivity (MIR) scale for the United States from 1988 to 2010

Abstract: Ozone reactivity scales play an important role in selecting which chemical compounds are used in products ranging from gasoline to pesticides to hairspray in California, across the United States and around the world. The California Statewide Air Pollution Research Center (SAPRC) box model that calculates ozone reactivity uses a representative urban atmosphere to predict how much additional ozone forms for each kilogram of compound emission. This representative urban atmosphere has remained constant since 1988,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(29 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…1). These cities have been used to characterize atmospheric reactivity across the US in previous air pollution studies (Carter, 1994(Carter, , 2010Venecek et al, 2018a, b). Simulations within each target city were carried out during peak summer air pollution events in 2010.…”
Section: Simulation Datesmentioning
confidence: 99%
“…1). These cities have been used to characterize atmospheric reactivity across the US in previous air pollution studies (Carter, 1994(Carter, , 2010Venecek et al, 2018a, b). Simulations within each target city were carried out during peak summer air pollution events in 2010.…”
Section: Simulation Datesmentioning
confidence: 99%
“…Several studies have used chamber experiments, mathematical models, and parameters such as the maximum incremental reactivity to investigate the O 3 production potential of select VOCs (Hakami et al, 2004;Huang et al, 2008;Kansal, 2009). These studies have shown that the contribution of a specific VOC to O 3 formation depends both on its intrinsic reactivity and its abundance and emission strength J o u r n a l P r e -p r o o f Journal Pre-proof (Kansal, 2009;Venecek et al, 2018). The O 3 production model based on inorganic trace gas and VOCs, including those discussed in detail herein, showed that the OH reactivity of formaldehyde, isoprene and alkenes were amongst the highest in San Antonio (Guo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The fugitive emission of VOCs in workshops can release into the outdoor air, which could impact the secondary formation of ambient ozone. The OFP values for individual VOC species are calculated as the product of their concentration and maximum incremental reactivity (MIR) reported from the literature [29]. Figure 4a shows the OFP values and chemical composition of VOCs emitted from the adhesive-making, adhesive-coating, and hot-pressing processes in the plywood manufacturing industry.…”
Section: Ozone Formation Potentials (Ofp) Of Vocsmentioning
confidence: 99%